Pros and Cons of Medical Cannabis Legalization in Indonesia - Fauziah, Eva; Runturambi, Arthur Josias Simon (Technium Social Sciences Journal, 2023)
Medical cannabis legalization policies continue to experience significant developments around the world. The adverse effects resulting from its misuse and the potential benefits that may be achieved from properly using this plant open up space for widespread public debate. Indonesia is one of the countries that consistently does not legalize the use of cannabis for both medical and recreational purposes. However, with the development of society, some movements encourage the government to open up space for the discourse on the legalization of medical cannabis. This study aims to describe the pros and cons of medical cannabis legalization in Indonesia. This study uses literature studies originating from scientific journals, books, policy documents, and medical reports related to the discourse on the legalization of medical cannabis in Indonesia. The problem of the pros and cons of this discourse has not yet found a clear spot because it is still limited and the difficulty of domestic research related to cannabis. Research is needed to assess the positive and negative impacts of cannabis use as a material consideration in deciding this policy. Specific regulations and technical guidelines from the government are also needed to support the development of cannabis research in Indonesia.